SEJARAH ISLAM DI PAKISTAN, IDE PEMBAHARUAN DAN PERJUANGAN MUHAMMAD ALI JINNAH - Ahsun Inayati; Indo Santalia; Wahyuddin G (Jurnal Ilmiah Hospitality, 2022)
Muhammad Ali Al Jinnah is a dynamic, creative, and tireless character and pioneer and the driving force behind the founding of Pakistan. Jinnah's ability and skill in realizing her ideas were supported by the basis of Islamic Religious Studies from her family and the knowledge she gained while in Europe. The first purpose of the founding of Pakistan was so that Indian Muslims could practice their religious teachings safely and peacefully, without that it would be impossible to create conformity of views among adherents of the major religions. His most prominent reform idea was in the political field. He wanted India to be freed from the grip of the British colonialists through decisive and revolutionary efforts. He did not like the way adopted by the Muslim League of the Indian National Congress party, namely the politics of obedience and loyalty to the British government.